Comparison of Slit Skin Smear (SSS) Examination and Clinical Criteria for Staging of Leprosy and Audit of the Process of SSS Examination in the Central Leprosy Clinic,Colombo. - Samarasekara, H.T (My University, 2004)
Accurate diagnosis and classification of leprosy patients into multibacillary (MB) and paucibacillary (PB) groups is critical in deciding the treatment regime for leprosy. Many leprosy endemic countries classify patients into MB and PB groups using clinical classification systems alone. However, bacteriological classification based on calculation of BI in slit skin smears (SSS) is superior in terms of specificity, SSS procedures are more costly and are usually practiced under poor laboratory conditions leading to inaccurate results.